Effect of organic amendments on the decontamination potential of heavy metals by Staphylococcus aureus and Bacillus cereus in soil contaminated with spent engine oil - Adeniyi O. Adeleye; Mohammed B. Yerima; Michael E. Nkereuwem; Victor O. Onokebhagbe; Peter G. Shiaka; Florence K. Amoo; Ibrahim K. Adam (Novel Research in Microbiology Journal)
This study was conducted to assess the decontamination of heavy metals of an environmental concern in spent engine oil (SEO) contaminated soil, through the adoption of Staphylococcus aureus and Bacillus cereus cocultures, isolated from Dutse mechanic village, Nigeria. About 1.5 kg of autoclaved soil was contaminated with SEO at three levels. The sterilized soil was then amended with compost, powdered cocoa pod husk (CPH), and powdered cow dung (CD). Subsequently, bio-augmentation with bacterial co-cultures (150 ml) was done. Heavy metal concentrations; Arsenic (As), Cadmium (Cd), Chromium (Cr), Nickel (Ni) and Lead (Pb) were estimated at the commencement, at the fifth and tenth week of the study. The factorial experiment was laid out in a completely randomized design (CRD). Results indicate that bio-stimulation adopted through the amendments did not have significant effects on the bacterial decontamination of soil especially at the 5th week (P> 0.05). CD only influenced the decontamination of Cd at 5% contamination level (0.0008 mg\ kg), compared with compost that recorded the least effect (0.00360 mg\ kg) at the 5th week. Meanwhile, CPH had the highest decontamination effect on Cr (0.004 and 0.000 mg\ kg) at 10% and 15% contamination levels; respectively, at the 5th week. However at the 10th week, complete removal of As was influenced by compost, CPH, and CD using 5%, 10% and 15% SEO contamination levels, respectively (P< 0.05). The decontamination efficacies of S. aureus and B. cereus recorded in this study is an indication of their potentialities for application in bioremediation of heavy metals.